Mirid bug outbreaks in multiple crops correlated with wide-scale adoption of Bt cotton in China - Lu, Y; Wu, K; Jiang, Y.; Xia, B; Li, P; Feng, H; Wyckhuys, Kris A.G.; Guo, Y (American Association for the Advancement of Science, 2010)
Long-term ecological effects of transgenic Bacillus thuringiensis (Bt) crops on nontarget pests have received limited attention, more so in diverse small holder based cropping systems of the developing world. Field trials conducted over 10 years in northern China show that mirid bugs (Heteroptera: Miridae) have progressively increased population sizes and acquired pest status in cotton and multiple other crops, in association with a regional increase in Bt cotton adoption. More specifically, our analyses show that Bt cotton has become a source of mirid bugs and that their population increases are related to drops in insecticide use in this crop. Hence, alterations of pest management regimes in Bt cotton could be responsible for the appearance and subsequent spread of nontarget pests at an agro-landscape level.